Opportunities and challenges of sequential extraction of silicon in contrasting soils - Stein, Mathias; Kilian Salas, Simone; Kleeberg, Reinhard; Jungkunst, Hermann F.; Schaller, Jörg (Frontiers in Environmental Science, 2026)
IntroductionThe importance of silicon for soil functioning has only recently received the attention it deserves in soil science (and ecology). To identify the actual effects of Si on ecosystem functioning, a precise knowledge about different Si soil fractions (plant-available, amorphous Si, and Si bound to organic matter, short-range ordered aluminosilicates (SROAS), or iron oxides/hydroxides) is required. Sequential extraction techniques are a common tool to quantify different soil fractions in soils of humid-temperate climates, whereas their reliability in other climatic zones or contrasting soils remains unclear. This study tested to what extend sequential extraction is applicable on soils from the High Andes and Amazon Basin, two contrasting regions with distinct soil formation processes.MethodsTo ensure method validity, we analyzed Si, iron (Fe), and aluminum (Al) in extracts and conducted X-ray diffraction (XRD) to detect mineral changes pre- and postextraction. Amorphous Si was more abundant in the High Andes soils, yet plantavailable Si was unexpectedly lower compared to Amazon Basin soils.ResultsSilicon occluded in Fe oxides/hydroxides or SROAS showed no differences between the two contrasting soils. XRD results revealed the following limitations: dithionite extraction did not completely remove Fe from hematite in Andean soils, and powder XRD lacked precision for amorphous Si quantification. Among the tested methods, CaCl2 extraction (for plant-available Si) and a two-step protocol—density separation for biogenic Si (bASi), followed by Tiron extraction for total amorphous Si (tASi)—were the most effective for these soils.DiscussionThese findings, with different methods not being able to characterize the soil used, underscore the need to refine Si extraction techniques for environments. Expanding methods originally developed in temperate soils is critical to understanding Si’s role in biogeochemical cycles and its broader significance for different ecosystem performance.